Dynamic Development of Family Law in Muslim Countries - Idham, Idham; Nur, Efa Rodiah; Hermanto, Agus (al-'adalah, 2022)
Abstract: Dynamic Development of Family Law in Muslim Countries. This article examines the dynamics of the development/renewal of Islamic family law in Muslim countries. The aim is to obtain a concrete picture of the development, from its original form, i.e conventional fiqh, to become positive law and apply it in Muslim countries. This research is classified as library research using a combination of historical and socio-anthropological approaches. Data were obtained from several secondary sources in the form of laws and regulations, books, articles, and many other documents related to the topic under study. The results of this study indicate that the role of the state in enforcing a legal system is absolute, in the sense that a law can be applied when it has been legislated as positive law. Apart from that, this study also found the fact that three models are applied in the development of family law in Muslim countries, namely; First, the state still applies the conventional legal system (fiqh). Second, the state carries out legal reforms within the school of thought. Third, the state makes its family law that is separate from religious norms to keep up with changes and developments in society.